Preparation method and application of powder carbomer
By controlling the acetic acid content and Fe element content in the unsaturated carboxylic acid during the preparation process of powder carbox, the existing powder carboxes have solved the problems of insufficient whiteness and metal impurities in the field of personal care, and the high quality and high safety of the product are achieved.
Patent Information
- Application Number
- CN202510000357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-25
AI Technical Summary
The existing powder cabo has problems such as insufficient whiteness and excessive metal impurities in the field of personal care, which affects the quality and safety of the product.
By strictly controlling the acetic acid content in unsaturated carboxylic acid, combining crosslinking agents and free radical initiators, polymerization reaction is carried out to prepare powder carbobos, controlling the Fe element content to be less than or equal to 1 ppm, and improving the transparency and whiteness of the product.
It effectively controls corrosion phenomena during the production process, improves the production pass rate of products, significantly improves the transparency and whiteness of products, and reduces the content of metal impurities.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer material preparation, and in particular to a preparation method of powdered carbomer and application thereof. Background Art
[0002] Powdered carbomer is a homopolymer or copolymer of acrylic acid, and is a very important rheology modifier. After neutralization, carbomer is an excellent gel matrix with excellent thickening, suspension and emulsification effects. It has good compatibility with other excipients and is mostly used as an additive for personal care and pharmaceutical excipients, especially in lotions, creams, and wash-free gels. Wash-free gels can be said to be an effective sterilization method to isolate viruses and protect people.
[0003] CN103755861A discloses a carbomer, which is mainly prepared by polymerizing acrylic acid with a water-soluble initiator in a mixed solvent of water and tert-butyl alcohol to obtain a powdered carbomer. The method provides a more inclusive, green and friendly aqueous phase reaction system by adding tert-butyl alcohol to obtain a carbomer with high quality performance.
[0004] CN105037606A discloses a carbomer resin, comprising the following raw materials in parts by mass: 10 to 110 parts of a carboxylic acid monomer, 0.01 to 1.5 parts of a cross-linking agent, 10 to 1000 parts of water; and 0.01 to 5.0 parts of other additives; wherein the carboxylic acid monomer is a carboxylic acid monomer having an olefinic double bond; the cross-linking agent is a monomer having two or more double bonds; and the other additives are one or more of sodium fatty alcohol benzene sulfonate, sodium fatty alcohol sulfate, fatty alcohol polyoxyethylene ether and its sulfate, hydrogen peroxide, persulfate, EDTA and its salts, and the like.
[0005] CN103483491A discloses a method for preparing powdered carbomer, which mainly uses an oil-soluble initiator to polymerize acrylic acid in a mixed solvent of ethyl acetate and cyclohexane to obtain a white powder of polyacrylic acid, which has a good thickening effect in the water phase and personal care fields.
[0006] In the field of personal care, product appearance, odor, and metal impurities have always been the focus of attention. Existing powdered carbomers still have problems such as product whiteness and excessive metal impurities. Summary of the invention
[0007] One of the purposes of the present invention is to provide a method for preparing powdered carbomer in view of the existing problems, strictly control the acetic acid content in the unsaturated carboxylic acid, reduce the Fe content in the product, and improve the transparency and whiteness of the product.
[0008] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0009] A method for preparing powdered carbomer comprises the following steps: in the presence of a crosslinking agent and a free radical initiator, unsaturated carboxylic acid is polymerized in a solvent to obtain a crosslinked polyunsaturated carboxylic acid polymer, and then post-treated to obtain powdered carbomer, wherein the content of acetic acid in the unsaturated carboxylic acid is 10-3000ppm, preferably 30-1000ppm, and more preferably 50-300ppm.
[0010] As a preferred solution, the mass fraction of the active substance in the powdered carbomer is ≥95wt%, preferably ≥97wt%, and the active substance is a product generated by a raw material unsaturated carboxylic acid and a cross-linking agent.
[0011] As a preferred solution, the Fe content in the powdered carbomer is less than or equal to 1 ppm.
[0012] The inventors found that acetic acid will inevitably cause corrosion in the actual production and use of powdered carbomer, that is, as the production time becomes longer, the Fe element content in the powdered carbomer product will increase, resulting in a decrease in the whiteness of the product. Use in facial mask formulas and shower gel formulas will result in a significant increase in product color numbers. Further, the inventors were surprised to find that there is a clear correlation between the content of acetic acid in the unsaturated carboxylic acid fed and the above-mentioned technical problems currently existing. Furthermore, through a large number of experimental studies, it was determined that when the unsaturated carboxylic acid fed contains 10-3000ppm of acetic acid, preferably 30-1000ppm of acetic acid, and more preferably 50-300ppm, the generation of corrosion can be effectively controlled, so that the Fe element content in the powdered carbomer product is less than or equal to 1ppm, which can significantly reduce the unqualified rate of the product.
[0013] The control of acetic acid content can be carried out by removing excess acetic acid by means of the distillation purification method or the freeze-crystallization-melting method described in CN118267737A, CN103880649A, and CN115970326A. Preferably, the distillation purification method is combined with the freeze-crystallization-melting method. The crude acrylic acid can be passed into the distillation unit, and the condensate is condensed and recovered to the acrylic acid recovery tank, and then sent to the acrylic acid crystallization feed tank 1 by an external pump, and then fed into the first-stage falling film crystallizer 1 by the first-stage falling film crystallizer feed pump, and the crystallization temperature is finally reduced to -15°C according to the gradient; the uncrystallized liquid phase enters the first-stage liquid phase collection tank 1, the system enters the sweating process, and the heat pump system enters the heating program, and the sweating temperature is finally increased to 13°C according to the gradient, and the high-purity product after sweating enters the first-stage product buffer tank 1. The acrylic acid-containing liquid phase from the primary liquid phase collection tank 1 enters the secondary falling film crystallizer 2 through the secondary falling film crystallizer feed pump, and the crystallization temperature is finally reduced to -15°C according to the gradient; the uncrystallized liquid phase enters the secondary liquid phase collection tank 2, the system enters the sweating process, the heat pump system enters the heating program, and the sweating temperature is finally increased to 13°C according to the gradient. The high-purity product after sweating enters the secondary product buffer tank 2, and the liquid phase in the secondary liquid phase collection tank 2 is circulated into the primary liquid phase collection tank 1 for reuse through the secondary falling film crystallizer liquid phase recycling pump. It is also possible to repeat the crystallization and sweating steps multiple times through a single-stage falling film crystallizer to gradually reduce the acetic acid content to below 3000ppm. It is not ruled out that the acetic acid content is controlled by mixing the refined acrylic acid and crude acrylic acid after the above-mentioned refinement.
[0014] In a technical solution of the present invention, the unsaturated carboxylic acid is acrylic acid or a combination of acrylic acid and a C4-C6 carboxylic acid containing a double bond, and the C4-C6 carboxylic acid containing a double bond is preferably one or more of maleic acid, itaconic acid, fumaric acid, methacrylic acid, crotonic acid, and aconitic acid.
[0015] In one technical solution of the present invention, the crosslinking agent comprises a substance containing at least two unsaturated carbon-carbon double bonds, preferably a multifunctional acrylate containing at least two polymerizable ethylenically unsaturated double bonds and / or a multialkenyl polyether containing at least two polymerizable ethylenically unsaturated double bonds.
[0016] Preferably, the multifunctional acrylate containing at least two polymerizable ethylenically unsaturated double bonds and the polyalkenyl polyether containing at least two polymerizable ethylenically unsaturated double bonds are obtained by esterification or etherification of linear or branched polyols.
[0017] As is well known in the art, the cross-linking agent is preferably one or more of trimethylolpropane diallyl ether, pentaerythritol triallyl ether, 1,6-hexanediol diacrylate, and triethylene glycol diacrylate.
[0018] Preferably, the amount of the cross-linking agent is 0.01-2% by mass of the active substance in the powdered carbomer, preferably 0.1-1.5%, more preferably 0.5-1%.
[0019] In a technical solution of the present invention, the free radical initiator comprises one or more of an organic peroxide compound, an azo compound, an inorganic persulfate compound and hydrogen peroxide, preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dodecyl peroxide, ammonium persulfate, sodium persulfate and hydrogen peroxide. As is well known in the art, the above initiators are commonly used in the art.
[0020] In a technical solution of the present invention, the solvent comprises alkanes and / or alkyl acetates, preferably C1-C10 alkanes and / or C1-C4 alkyl acetates; preferably, the alkanes comprise one or more of n-hexane, cyclohexane, n-heptane, cycloheptane, and n-decane; preferably, the C1-C4 alkyl acetates comprise one or more of ethyl acetate, butyl acetate, ethyl propionate, and butyl propionate. As is well known in the art, the above solvents are commonly used solvents in the art.
[0021] As a preferred solution, the post-processing of the present invention includes but is not limited to separation, drying, etc.
[0022] In a technical solution of the present invention, the preparation method comprises the following steps:
[0023] S1: adding the unsaturated carboxylic acid, the crosslinking agent, and the optional dispersant into a solvent and mixing to obtain a reaction system;
[0024] S2: adding a free radical initiator to the reaction system, carrying out a polymerization reaction, cooling, filtering, separating, washing and drying to obtain powdered carbomer.
[0025] In a technical solution of the present invention, a dispersant is optionally added to S1; preferably, the dispersant is a nonionic emulsifier with an HLB value of 2-6.5, preferably one or more of propylene glycol monostearate (HLB value 3.4), sorbitan stearate (HLB value 4.7), sorbitan tristearate (HLB value 2.1) and diethylene glycol monolaurate (HLB value 6.1). It is well known in the art that the above dispersants are commonly used dispersants in the art.
[0026] In a technical solution of the present invention, the polymerization reaction temperature in S2 is 50-80°C.
[0027] Another object of the present invention is to provide a use of powdered carboplatin.
[0028] A use of powdered carbomer, wherein the powdered carbomer is used in the field of personal care, and is preferably used as a transparent gel medium.
[0029] The main structure of powdered carbomer is polyacrylic acid. When the polymer is added to an aqueous system, along with the addition of alkaline substances, the carboxylic acid on the main chain of polyacrylic acid becomes a carboxylate group. Since the carboxylate group is negatively charged, the charge repulsion causes the main chain of the polymer to stretch and fill the space of the system. At the same time, the carboxylate group and water form hydrogen bonds, which greatly restricts the free movement of water molecules, thereby increasing the viscosity of the entire system.
[0030] Compared with the prior art, the positive effects of the present invention are:
[0031] (1) It can effectively control the corrosion phenomenon in the production process and improve the product production qualification rate;
[0032] (2) Adding a small amount of this product into the formulation system can achieve the desired transparency and viscosity. DETAILED DESCRIPTION
[0033] In order to better implement the present invention, the present invention is further described below in conjunction with embodiments, but the embodiments are not intended to limit the present invention.
[0034] The main raw materials and information used in this example are shown in Table 1 below:
[0035] Table 1
[0036]
[0037] The main equipment information used in this embodiment is shown in Table 2 below:
[0038] Table 2
[0039]
[0040]
[0041] The acetic acid test in unsaturated carboxylic acids is carried out in accordance with the national standard GBT 17529.1-2023. The chromatographic column selected is a capillary column.
[0042] The specific method for testing acetic acid in unsaturated carboxylic acids is as follows: under selected working conditions, the sample is vaporized and then separated by a chromatographic column, detected by a hydrogen flame ionization detector, and quantified by an area normalization method.
[0043] Combustion gas: high-purity hydrogen, with a volume fraction of not less than 99.99%. It needs to be treated with a dehydration device, silica gel, molecular sieve or activated carbon before use;
[0044] Carrier gas: high-purity nitrogen, with a volume fraction of not less than 99.99%. It needs to be treated with a dehydration device, silica gel, molecular sieve or activated carbon before use;
[0045] Air: Free of corrosive impurities, and must be depleted and dehydrated before use.
[0046] Instrument: Gas chromatograph (Agilent 7820A) equipped with hydrogen flame ionization detector, automatic sample injector, injection volume 1uL.
[0047] The chromatographic analysis conditions are as follows: Other chromatographic columns and chromatographic operating conditions that can achieve the same degree of separation can be used.
[0048] Chromatographic column: capillary column, column length / column inner diameter / liquid film thickness: 30m*0.53mm*1.0um;
[0049] Fixative: polyethylene glycol modified with nitroterephthalic acid;
[0050] Vaporization chamber temperature: 200℃;
[0051] Column box temperature: initial temperature 120°C, hold for 3 min, heating rate 20°C / min, final temperature 190°C, hold for 22 min, equilibrium time 3 min;
[0052] Detector temperature: 220°C;
[0053] Carrier gas flow rate: nitrogen, 25 mL / min;
[0054] Gas flow rate: hydrogen, 30mL / min;
[0055] Gas flow rate: air, 400mL / min;
[0056] Split ratio: 10:1;
[0057] The thickening effect, transparency, whiteness and Fe content in the present invention are tested by the following method:
[0058] Thickening efficiency test method: add 208.5g of deionized water to a 300ml plastic straight bottle with a diameter of 8cm, then add 1.4g of the powdered carbomer of the present invention, and place it for 8 hours to allow it to fully absorb water and swell. Add a stirring paddle, start stirring, slowly add 18% sodium hydroxide aqueous solution, stir at 800rpm for 40-60min, and adjust its pH value to 7.5±0.2. Put it in a constant temperature water bath, let it stand for 8 hours until it is stable, and test its 20rpm viscosity.
[0059] Transparency test method: Take an appropriate amount of the prepared stable sample and put it into a centrifuge tube. Put the centrifuge tube into the centrifuge, set the speed to 5000rpm, and the centrifugation time to 10min. After the centrifugation is completed, carefully take the sample and put it into a cuvette (to prevent the introduction of bubbles). Then put the cuvette into the spectrophotometer to measure the transparency.
[0060] Whiteness test method: Shenzhen Puyun PY-E634 whiteness tester and PY-E634B powder constant pressure sampler. 1. Sampling, put the powder in the PY-E634B powder sampler, fill it up and press it with glass to form a flat surface without pits. 2. Put it in the test port of the whiteness meter and press the test button to display the whiteness of the powder. 3. After the test is completed, measure the test data 3 times and take the average.
[0061] Fe element content test method: VISTA-MPX inductively coupled plasma emission spectrometer (Varian, USA), high-resolution step grating, vertical observation torch, wavelength range 167-785nm, charge coupled device (CCD) detector, glass concentric atomizer, frequency 40MHz, power 0.9kW, observation height 13mm, carrier gas pressure 220kPa, peristaltic pump speed 15rpm. The powder sample was ashed at 600℃ and then moistened with a small amount of high-purity water. 2mL of HNO3(1+1)+HClO4 solution was added and slowly heated to near boiling on an electric furnace. When the solution became clear, 5mL of HCl (4%) was added and kept near boiling on an electric furnace for 10min, and then the solution was transferred to a polytetrafluoroethylene beaker. Continue to place the sample on a 78°C hot plate and heat to concentrate the solution to about 1 mL. Stop heating, cool, dilute to volume with 2% HNO3 in a 25 mL polyethylene volumetric flask, shake well, and make a reagent blank for determination by ICP-AES.
[0062] Example 1
[0063] The powdered Carbomer A1 was prepared, and its synthetic formula composition is as shown in Table 3:
[0064] Table 3
[0065]
[0066]
[0067] In this embodiment, the refined acrylic acid prepared by the freeze-crystallization-thawing method of Wanhua Chemical Group Co., Ltd. was tested before feeding, and the acetic acid content of the feed was 100 ppm.
[0068] The steps for synthesizing powdered carbomer using this formula are as follows:
[0069] 2500 kg of cyclohexane and 2500 kg of ethyl acetate were added to a 15 cubic stainless steel polymerization reactor, and then 4 kg of sorbitan stearate was added. The mixture was mixed evenly and replaced with nitrogen for more than 30 minutes to replace the oxygen content in the system to 1×10 - 7 mg / L or less;
[0070] 992 kg of acrylic acid and 8 kg of trimethylolpropane diallyl ether were added to the above polymerization kettle, mixed evenly, and nitrogen was continuously passed to replace oxygen;
[0071] The reaction temperature was raised to 78°C, and 6 kg of benzoyl peroxide (for initiation) was added to the polymerization kettle to start the polymerization reaction, which was continued for 5 h until the reaction was complete.
[0072] The reaction temperature was maintained at 78°C, and a mixed solution of 125 kg of ethyl acetate, 125 kg of cyclohexane and 2 kg of benzoyl peroxide (to eliminate residual monomers) was added, and the mixture was further treated for 2 hours to eliminate residual monomers. After the treatment was completed, the mixture was cooled to room temperature to obtain a suspension solution of an unsaturated carboxylic acid polymer;
[0073] The obtained suspension was filtered through a plate-and-frame filter press to obtain a white precipitate, and the white precipitate was washed three times with a mixed solvent (cyclohexane:ethyl acetate=1:1 mass ratio), and filtered after each washing to finally obtain a solvent-containing white polymer;
[0074] The white polymer containing solvent was transferred to a dryer, maintained at 90°C, and dried under negative pressure for 24 hours to obtain powdered Carbopol A1. Ten batches were produced continuously to test product performance, whiteness and Fe content. The test data parameters are shown in Table 4 below:
[0075] Table 4
[0076]
[0077]
[0078] Example 2
[0079] Powdered Carbomer B1 was prepared, and its synthetic formula composition is as shown in Table 5:
[0080] Table 5
[0081]
[0082] In this embodiment, the refined acrylic acid prepared by the freeze-crystallization-thawing method of Wanhua Chemical Group Co., Ltd. and acrylic acid with an acetic acid content of 3500 ppm were mixed and fed before testing. The acetic acid content of the feed was tested to be 1068 ppm.
[0083] The steps for synthesizing powdered carbomer using this formula are as follows:
[0084] 1700 kg cyclohexane and 3400 kg ethyl acetate were added to a 15 cubic stainless steel polymerization reactor, and then 2 kg propylene glycol monostearate was added. The mixture was mixed evenly and replaced with nitrogen for more than 30 minutes to replace the oxygen content in the system to 1×10-7 mg / L or less;
[0085] 532 kg of refined acrylic acid, 212 kg of unrefined acrylic acid, 250 kg of methacrylic acid, and 6 kg of tripentaerythritol triallyl ether were added into the kettle, mixed evenly, and nitrogen was continuously passed to replace oxygen;
[0086] The reaction temperature was raised to 62°C, and 2.2 kg of dodecyl peroxide was added to start the polymerization reaction, which lasted for 7 hours until the reaction was complete.
[0087] The reaction temperature was maintained at 62°C, and a mixed solution of 360 kg of ethyl acetate, 180 kg of cyclohexane and 2 kg of dodecyl peroxide was added, and the mixture was further treated for 2 hours to eliminate the residual monomers. After the treatment was completed, the mixture was cooled to room temperature to obtain a suspension solution of an unsaturated carboxylic acid polymer;
[0088] The obtained suspension was filtered through a plate-and-frame filter press to obtain a white precipitate, and the white precipitate was washed three times with a mixed solvent (cyclohexane:ethyl acetate=1:2 mass ratio), and filtered after each washing to finally obtain a solvent-containing white polymer;
[0089] The white polymer containing solvent was transferred to a dryer, maintained at 90°C, and dried under negative pressure for 24 hours to obtain powdered Carbopol B1. Ten batches were produced continuously to test product performance, whiteness and Fe content. The test data parameters are shown in Table 6 below:
[0090] Table 6
[0091]
[0092]
[0093] Example 3
[0094] Powdered Carbomer C1 was prepared, and its synthetic formula composition is as shown in Table 7:
[0095] Table 7
[0096]
[0097] In this embodiment, the refined acrylic acid prepared by the freeze-crystallization-thawing method of Wanhua Chemical Group Co., Ltd. and acrylic acid with an acetic acid content of 3500 ppm were mixed and fed before testing. The acetic acid content of the feed was tested to be 1980 ppm.
[0098] The steps for synthesizing powdered carbomer using this formula are as follows:
[0099] 2900kg cyclohexane and 1450kg ethyl acetate were added to a 15 cubic stainless steel polymerization reactor, and then 9kg sorbitan tristearate was added, mixed evenly, and replaced with nitrogen for more than 30 minutes to replace the oxygen content in the system to 1×10 -7 mg / L or less;
[0100] 548 kg of refined acrylic acid, 448 kg of unrefined acrylic acid, and 12 kg of 1,6-hexanediol diacrylate were added into the kettle, mixed evenly, and nitrogen was continuously passed to replace oxygen;
[0101] The reaction temperature was raised to 54°C, and 6.8 kg of azobisisobutyronitrile was added to the four-necked flask to start the polymerization reaction, which lasted for 9 hours until the reaction was complete.
[0102] The reaction temperature was maintained at 54°C, and a mixed solution of 100 kg of ethyl acetate, 200 kg of cyclohexane and 2 kg of azobisisobutyronitrile was added, and the mixture was further treated for 2 hours to eliminate the residual monomers. After the treatment was completed, the mixture was cooled to room temperature to obtain a suspension solution of the unsaturated carboxylic acid polymer;
[0103] The obtained suspension was filtered through a plate-and-frame filter press to obtain a white precipitate, and the white precipitate was washed three times with a mixed solvent (cyclohexane:ethyl acetate=2:1 mass ratio), and filtered after each washing to finally obtain a solvent-containing white polymer;
[0104] The white polymer containing solvent was transferred to a dryer, maintained at 90°C, and dried under negative pressure for 24 hours to obtain powdered Carbopol C1. Ten batches were produced continuously to test product performance, whiteness and Fe content. The test data parameters are shown in Table 8 below:
[0105] Table 8
[0106] Test batches and items Viscosity / cp transparency / % Whiteness Fe content C1 batch 45500 93 93 <1ppm C2 batch 46000 95 94 <1ppm C3 batch 46100 94 95 <1ppm C4 batch 44500 92 93 <1ppm C5 batch 45800 93 93 <1ppm C6 batch 47000 95 93 <1ppm C7 batch 45000 92 93 <1ppm C8 batch 45900 93 93 <1ppm C9 batch 46000 92 94 <1ppm C10 batch 45800 93 93 <1ppm
[0107] Example 4
[0108] Powdered Carbomer D1 was prepared, and its synthetic formula composition is as shown in Table 9:
[0109] Table 9
[0110]
[0111]
[0112] In this embodiment, acrylic acid with an acetic acid content that meets the ratio requirement is tested before feeding. Refined acrylic acid prepared by the freeze-crystallization-thawing method of Wanhua Chemical Group Co., Ltd. and acrylic acid with an acetic acid content of 3500 ppm are mixed and fed. The acetic acid content of this feed is tested to be 3000 ppm.
[0113] The steps for synthesizing powdered carbomer using this formula are as follows:
[0114] 1880 kg cyclohexane and 2820 kg ethyl acetate were added to a 15 cubic stainless steel polymerization reactor, and then 7 kg diethylene glycol monolaurate was added. The mixture was mixed evenly and replaced with nitrogen for more than 30 minutes to replace the oxygen content in the system to 1×10 - 7 mg / L or less;
[0115] 840 kg of unrefined acrylic acid, 60 kg of refined acrylic acid, 8 kg of pentaerythritol triallyl ether and 10 kg of triethylene glycol diacrylate were added into the kettle, mixed evenly, and nitrogen was continuously passed to replace oxygen;
[0116] The reaction temperature was raised to 58°C, and 7 kg of benzoyl peroxide was added to start the polymerization reaction, which lasted for 8 hours until the reaction was complete.
[0117] The reaction temperature was maintained at 58°C, and a mixed solution of 150 kg of ethyl acetate, 100 kg of cyclohexane and 2 kg of benzoyl peroxide was added, and the mixture was further treated for 2 hours to eliminate the residues. After the treatment was completed, the mixture was cooled to room temperature to obtain a suspension solution of the unsaturated carboxylic acid polymer;
[0118] The obtained suspension was filtered through a plate-and-frame filter press to obtain a white precipitate, and the white precipitate was washed three times with a mixed solvent (cyclohexane:ethyl acetate=1:1.5 mass ratio), and filtered after each washing to finally obtain a solvent-containing white polymer;
[0119] The white polymer containing solvent was transferred to a dryer, maintained at 90°C, and dried under negative pressure for 24 hours to obtain powdered Carbopol D1. Ten batches were produced continuously to test product performance, whiteness and Fe content. The test data parameters are shown in Table 10 below:
[0120] Table 10
[0121]
[0122]
[0123] Comparative Example 1
[0124] A powdered carbomer E1 was prepared. Compared with Example 1, the difference was that acrylic acid with an acetic acid content of 3500 ppm produced by Wanhua Chemical Group Co., Ltd. was used as the raw material. Powdered carbomer E1 was prepared according to the method of Example 1, and its test data parameters are shown in Table 11 below:
[0125] Table 11
[0126]
[0127]
[0128] The following application examples 1-2 are examples 1-4 using the cross-linked polyunsaturated carboxylic acid polymer, and are compared with comparative example E1. The items and methods required for testing are as follows:
[0129] 1) Thickening efficiency: Add the same amount of powdered carbopol into the system and observe the viscosity of the system at 20 rpm at 20°C, in cp;
[0130] 2) Transparency test: measured using a Unico 7200 spectrophotometer, 100% is optimal;
[0131] 3) Storage stability: The prepared formula was placed in a 50°C oven for 14 days to observe the changes in the appearance of the system; judgment criteria: 5 points for good storage stability and 1 point for poor storage stability;
[0132] 4) Color number test: The prepared formula was placed in a 50°C oven for 14 days, and its color number was tested using an HSY-0901C-1 solution color tester (colorimeter).
[0133] Application Example 1
[0134] In the transparent shower gel formula, the unsaturated carboxylic acid polymers A1-D1 synthesized by the present invention were tested and compared with the comparative examples E1 and E10.
[0135] The formula of transparent shower gel is as shown in Table 12:
[0136] Table 12
[0137]
[0138] To make this clear body wash recipe:
[0139] 1) Phase A: In a 250 ml beaker, dissolve 4.0 g potassium hydroxide in 18 g water and heat to 85°C;
[0140] 2) Phase B: In a 250 ml beaker, add 8.0 g glycerol and 0.4 g unsaturated carboxylic acid polymer to 30 g water and mix well;
[0141] 3) Add 7.55 g of lauric acid to phase B, heat to 85°C, stir to melt, keep constant temperature at 85°C, and continue stirring;
[0142] 4) Maintaining 85°C, slowly add phase A to phase B and stir for 60 minutes;
[0143] 5) Cool the mixture of phases A and B to 60° C., add 20 g of sodium laureth sulfate and 12 g of cocamidopropyl betaine in sequence, and stir at the same temperature for 60 min to mix evenly;
[0144] 6) Cool down to 45°C, add 0.05 g of methylisothiazolinone, stir evenly, and cool to room temperature.
[0145] In this formula, the powders Carbomer A1-D1 synthesized in the comparative examples and the comparative products E1 and E10 were compared to obtain the following results in Table 13:
[0146] Table 13
[0147] Test items A1 B1 C1 D1 E1 E10 Viscosity / CP 5500 5200 5100 5300 5200 5420 transparency / % 94 93 93 94 92 90 Color number after heat storage 5 6 4 5 13 47 Storage stability 5 5 5 5 5 5
[0148] As can be seen from the table, the powder Carbopol A1-D1 of the present invention also has good thickening efficiency and good chromaticity in the transparent shower gel formula. For the comparative examples E1 and E10, as the Fe content increases, the color number increases significantly after heat storage.
[0149] Application Example 2
[0150] In the skin mask formula, the synthesized powders of Carbomer A1-D1 of the present invention were tested and compared with comparative products E1 and E10.
[0151] The skin mask formula is as shown in Table 14:
[0152] Table 14
[0153]
[0154]
[0155] The steps to make this skin mask recipe are:
[0156] 1) Add 60g of deionized water to a 250ml beaker and heat it to 70°C;
[0157] 2) Add 5 g of polydimethylsiloxane and 2 g of PEG-10-dimethylsiloxane into a beaker while stirring until they are evenly mixed;
[0158] 3) The mixed solution in the beaker was cooled to 50°C, and 1.0g of butanediol, 0.8g of glycerol and 0.2g of unsaturated carboxylic acid polymer were added while stirring and mixed evenly;
[0159] 4) Cool the mixed solution in the beaker to room temperature and homogenize the mixed solution in the beaker with a homogenizer at a speed of 20,000 rpm for 30 minutes to make it more evenly mixed;
[0160] 5) Keep stirring, slowly add 30g polyurethane-10, 0.2g EDTA-2Na and 0.3g octyl glycol to the mixed solution in the beaker, mix well, add 0.5g diethanolamine, change the rotation speed as the viscosity increases, make the whole neutralization uniform, and adjust the pH value to 5.2-5.5.
[0161] In this formula, the powders Carbomer A1-D1 synthesized in the comparative examples and the comparative products E1 and E10 were compared to obtain the following results in Table 15:
[0162] Table 15
[0163] Test items A1 B1 C1 D1 E1 E10 Viscosity 5700 5760 5600 5750 5920 6030 transparency 77% 73% 73% 75% 64% 57% Color number after heat storage 10 11 9 12 26 59
[0164] As can be seen from the table, the powder Carbopol A1-D1 of the present invention also has good thickening efficiency in the skin mask formula without affecting transparency. For comparative examples E1 and E10, as the Fe content increases, the color number increases significantly after heat storage.
[0165] The above embodiments are preferred implementation methods of the present invention, but the present invention is not limited to the above implementation methods. Any other changes, modifications, simplifications, and substitutions made without departing from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing powdered carbomer, comprising the following steps: In the presence of a crosslinking agent and a free radical initiator, unsaturated carboxylic acid is polymerized in a solvent to obtain a crosslinked polyunsaturated carboxylic acid polymer, which is then post-treated to obtain powdered carbomer, wherein the content of acetic acid in the unsaturated carboxylic acid is 10-3000ppm, preferably 30-1000ppm, and more preferably 50-300ppm.
2. The method according to claim 1, characterized in that The mass fraction of the active substance in the powdered carbomer is ≥95wt%, preferably ≥97wt%, and the active substance is a product generated by the raw material unsaturated carboxylic acid and a cross-linking agent.
3. The method according to claim 1 or 2, characterized in that: The Fe content in the powdered carbopol is less than or equal to 1 ppm.
4. The method according to any one of claims 1 to 3, characterized in that The unsaturated carboxylic acid is acrylic acid or a combination of acrylic acid and a C4-C6 carboxylic acid containing a double bond. The C4-C6 carboxylic acid containing a double bond is preferably one or more of maleic acid, itaconic acid, fumaric acid, methacrylic acid, crotonic acid, and aconitic acid.
5. The method according to any one of claims 1 to 4, characterized in that The crosslinking agent comprises a substance containing at least two unsaturated carbon-carbon double bonds, preferably a multifunctional acrylate containing at least two polymerizable ethylenically unsaturated double bonds and / or a polyalkenyl polyether containing at least two polymerizable ethylenically unsaturated double bonds; preferably, the multifunctional acrylate containing at least two polymerizable ethylenically unsaturated double bonds and the polyalkenyl polyether containing at least two polymerizable ethylenically unsaturated double bonds are obtained by esterification or etherification of linear or branched polyols; more preferably, the crosslinking agent is selected from one or more of trimethylolpropane diallyl ether, pentaerythritol triallyl ether, 1,6-hexanediol diacrylate, and triethylene glycol diacrylate.
6. The method according to any one of claims 1 to 5, characterized in that The amount of the cross-linking agent used is 0.01-2% of the mass of the active substance in the powdered carbomer, preferably 0.1-1.5%, more preferably 0.5-1%.
7. The method according to any one of claims 1 to 6, characterized in that The free radical initiator comprises one or more of organic peroxide compounds, azo compounds, inorganic persulfate compounds and hydrogen peroxide, preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, dodecyl peroxide, ammonium persulfate, sodium persulfate and hydrogen peroxide; the solvent comprises alkanes and / or alkyl acetates, preferably C1-C10 alkanes and / or C1-C4 alkyl acetates; preferably, the alkanes comprise one or more of n-hexane, cyclohexane, n-heptane, cycloheptane and n-decane; preferably, the C1-C4 alkyl acetates comprise one or more of ethyl acetate, butyl acetate, ethyl propionate and butyl propionate.
8. The method according to any one of claims 1 to 7, characterized in that The preparation method comprises the following steps: S1: adding the unsaturated carboxylic acid, the crosslinking agent, and the optional dispersant into a solvent and mixing to obtain a reaction system; S2: adding a free radical initiator to the reaction system, carrying out a polymerization reaction, cooling, filtering, separating, washing and drying to obtain powdered carbomer.
9. The method according to claim 8, characterized in that The polymerization reaction temperature in S2 is 50-80°C.
10. Use of the powdered carbomer prepared by the method according to any one of claims 1 to 9, characterized in that: The powdered carbopol is used in the field of personal care, and is preferably used as a transparent gel medium.
Citation Information
Patent Citations
Carbomer and preparation method thereof
CN103483491A
Carbomer and preparation method thereof
CN103755861A
Method for preparing high-yield ice crystal grade acrylic acid
CN103880649A
Carbomer resin and preparing method thereof
CN105037606A
Crystallizer for high-purity acrylic acid
CN115970326A